The potential for production of freeze-dried oral vaccines using alginate hydrogel microspheres as protein carriers - D.M. Hariyadi (Elsevier, 2014)
Oral administration of dry vaccine formulations is acknowledged to offer major clinical and logistical benefits by eliminating the cold chain required for liquid preparations. A model antigen, bovine serum albumin (BSA) was encapsulated in alginate microspheres using aerosolisation. Hydrated microspheres 25 to 65 µm in size with protein loading of 3.3 % w/w were obtained. Environmental scanning electron microscopy indicated a stabilizing effect of encapsulated protein on alginate hydrogels revealed by an increase in dehydration resistance. Freeze drying of alginate microspheres without use of a cryoprotectant resulted in fragmentation and subsequent rapid loss of the majority of the protein load in simulated intestinal fluid in 2 h, whereas intact microspheres were observed following freeze-drying of BSA-loaded microspheres in the presence of maltodextrin. BSA release from freeze-dried preparations was limited to less than 7 % in simulated gastric fluid over 2 h, while 90 % of the protein load was gradually released in simulated intestinal fluid over 10 h. SDS-PAGE analysis indicated that released BSA largely preserved its molecular weight. These findings demonstrate the potential for manufacturing freeze-dried oral vaccines using alginate microspheres.